Evidence against the structural gene encoding type II collagen (COL2A1) as the mutant locus in achondroplasia. Issue 1 (February 1986) - Ogilvie, D; Wordsworth, P; Thompson, E; Sykes, B
Abstract : The structure of the locus encoding the major cartilage collagen gene (COL2A1) was studied in a total of 19 cases of achondroplasia. No gross rearrangements were seen. The segregation of COL2A1 was examined in three affected kindreds using restriction site and length variants as genetic markers. In two kindreds discordant segregation between the achondroplasia and COL2A1 loci was demonstrated. Paternity/maternity was confirmed using a 'minisatellite' core sequence probe which reveals cross hybridising polymorphic loci.